Mapping global research trends in power quality for industrial electrical systems: a bibliometric analysis (2016–2024) - Noriega Angarita, Eliana; Sousa Santos, Vladimir; D. Donolo, Pablo; Solorio Aguila, Edgar; Garcia Garcia, Endy; Hernandez Tomas, Johan; Garduno Leon, Victor; Rivera Ramos, Jose (Bulletin of Electrical Engineering and Informatics, 2025)
This paper analyzes trends in electrical power quality (PQ) in industrial systems through a bibliometric approach to identify key topics, prominent authors, and patterns of international collaboration that may guide future research. PQ disturbances can significantly affect operational continuity, energy efficiency, and equipment lifespan in industrial electrical systems (IES), making it essential to map the research landscape to support technological and strategic responses. The study reviews 103 articles from the Scopus database for the period 2016–2024, applying relevance and currency criteria. VOSviewer® was used to conduct the analysis, employing keyword co-occurrence networks and bibliographic coupling to visualize thematic, collaborative, and citation relationships. Results indicate a strong research focus on harmonic distortion, voltage disturbances, and artificial intelligence applications for diagnosis and mitigation. India leads in scientific production, while IEEE Access is the most influential source. Despite growing interest, the study identifies limited international collaboration and thematic fragmentation, which may hinder comprehensive solutions. The findings highlight the need to expand collaboration networks, standardize methodologies, and integrate underexplored topics into mainstream PQ studies, strengthening the ability of industrial systems to address emerging challenges and improve performance, resilience, and reliability.